Kombucha and its dehydrated and freeze-dried derivatives : physicochemical and microbiological characterization and in vivo toxicity evaluation - Correia Santana, Débora (2024)
Fil: Correia Santana, Débora. Universidade Vila Velha. Programa de Pós-Graduação em Biotecnologia Vegetal; Brasil.